Younger vampire bats (Desmodus rotundus) are more likely than adults to explore novel objects - Carter, Gerald G. (PLoS One, 2018)
The effects of age on neophobia and exploration are best described in birds and primates, and broader comparisons require reports from other taxa. Here we present data showing age-dependent exploration in a long-lived social species, the common vampire bat (Desmodus rotundus). A previous study found that vampire bats regurgitated food to partners trapped in a cage. Interestingly, while only a few adult bats visited the trapped bat, in every trial all or most of the eight young males in the colony would visit the trapped bat without feeding it. To test whether this behavioral difference resulted from age class differences in exploration, we compared responses of the bats to a trapped conspecific versus an inanimate novel object. Some adults and young showed interest in trapped conspecifics, but only the young males explored the novel objects. Additional novel object tests in a second captive colony showed that higher rates of novel object exploration were shown by young of both sexes. Our results corroborate past findings from other mammals and birds that age predicts exploration. If age-dependent exploration is indeed adaptive, then the role of age as a predictor of exploration tendency should depend on species-specific life history traits. Finally, because younger vampire bats also appear to have higher exposure to pathogens such as rabies virus, there may be implications for pathogen transmission if younger and more exploratory vampire bats are more likely to feed on novel hosts.